Maps of experience : the anchoring of land to story in Secwepemc discourse - Palmer, Andie Diane N. (Anthropological horizons., 2005)
Palmer's analysis of ways of listening and conveying information within the Alkali Lake community brings new insights into indigenous language and culture, as well as to the study of oral history, ethnohistory, experimental ethnography, and discourse analysis.